Changes of alveolar bone density around the abutment teeth in patients wearing removable partial dentures depending on Kennedy classification - Kovačević Pavičić, Daniela (Array, 2009)
Abstract: The aim was to study the influence of Kennedy classification on alveolar bone density changes around the abutment teeth of removable partial denture (RPD) clasp and rests. A total of 50 examinees of both gender wearing RPDs were included in the study. Changes of bone density around the abutment teeth were determined by an intraoral microdensitometry method. Standard retroalveolar radiographs were obtained twice: the first one at the RPD delivery and the second one after a period of 3 month of denture wearing. The copper stepwedge consisting of 5 steps (0.1–0.1 mm) was attached to the radiograph prior to exposure in order to calibrate it. Seven regions of interest (ROI) in different position close to the root of the abutment tooth were selected on each radiograph, all 10 pixels in size. Grey levels of each ROI were measured and were converted into equivalents of the copper stepwedge thickness using the third degree polynomial in order to compare the difference of bone density between the two radiographs. The results indicated that Kennedy classification had no significant influence on the change of bone density in RPD patients during first 3 month of RPD wearing (ANOVA: p>0.05)